2021
DOI: 10.3389/fmedt.2021.719909
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Internal Carotid Artery Morphology on in silico Stent-Retriever Thrombectomy Outcome

Abstract: The aim of this work is to propose a methodology for identifying relationships between morphological features of the cerebral vasculature and the outcome of in silico simulations of thrombectomy, the mechanical treatment for acute ischemic stroke. Fourteen patient-specific cerebral vasculature segmentations were collected and used for geometric characterization of the intracranial arteries mostly affected by large vessel occlusions, i.e., internal carotid artery (ICA), middle cerebral artery (MCA) and anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…In addition to physical models, computational modeling is gaining attention and likely to have an increasing role in medical device development ( 57 , 90 92 ). Finite element modeling is recommended by the FDA, in the guidance for non-clinical testing of stents and associated delivery systems, as a means of performing stress and fatigue analysis on the devices seeking approval ( 93 ).…”
Section: Discussion and Recommendations For Future Advancementsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to physical models, computational modeling is gaining attention and likely to have an increasing role in medical device development ( 57 , 90 92 ). Finite element modeling is recommended by the FDA, in the guidance for non-clinical testing of stents and associated delivery systems, as a means of performing stress and fatigue analysis on the devices seeking approval ( 93 ).…”
Section: Discussion and Recommendations For Future Advancementsmentioning
confidence: 99%
“…Recent publications from the INSIST project (IN- Silico trials for treatment of acute Ischemic Stroke) report the development of a platform where computational simulations of thrombosis and thrombolysis, thrombectomy, perfusion, and brain tissue infarction are carried out on “virtual patients” ( 57 , 94 ). These “virtual patients” include clinically representative characteristics such as clot properties, vessel geometries, and clinical record.…”
Section: Discussion and Recommendations For Future Advancementsmentioning
confidence: 99%
See 2 more Smart Citations
“…These segments consist of a C1 (cervical), C2 (petrous or horizontal), C3 (lacerum), C4 (cavernous), C5 (clinoid), C6 (ophthalmic or supraclinoid), and C7 (communicating or terminal) parts. Many studies have reported that anatomical variations of the ICA can be associated with various neurovascular diseases and thus, can consequently complicate endovascular and surgical approaches [4,10,12,14,16,18,21]. For example, variant ICAs have been reported to result in complications during treatment of traumatic cavernous sinus stulas (TCCF) [5,13,22].…”
Section: Introductionmentioning
confidence: 99%